The role of glypicans in Wnt inhibitory factor-1 activity and the structural basis of Wif1's effects on Wnt and Hedgehog signaling. - Andrei Avanesov; Shawn M Honeyager; Jarema Malicki; Seth S Blair (PLoS Genetics)
Proper assignment of cellular fates relies on correct interpretation of Wnt and Hedgehog (Hh) signals. Members of the Wnt Inhibitory Factor-1 (WIF1) family are secreted modulators of these extracellular signaling pathways. Vertebrate WIF1 binds Wnts and inhibits their signaling, but its Drosophila melanogaster ortholog Shifted (Shf) binds Hh and extends the range of Hh activity in the developing D. melanogaster wing. Shf activity is thought to depend on reinforcing interactions between Hh and glypican HSPGs. Using zebrafish embryos and the heterologous system provided by D. melanogaster wing, we report on the contribution of glypican HSPGs to the Wnt-inhibiting activity of zebrafish Wif1 and on the protein domains responsible for the differences in Wif1 and Shf specificity. We show that Wif1 strengthens interactions between Wnt and glypicans, modulating the biphasic action of glypicans towards Wnt inhibition; conversely, glypicans and the glypican-binding "EGF-like" domains of Wif1 are required for Wif1's full Wnt-inhibiting activity. Chimeric constructs between Wif1 and Shf were used to investigate their specificities for Wnt and Hh signaling. Full Wnt inhibition required the "WIF" domain of Wif1, and the HSPG-binding EGF-like domains of either Wif1 or Shf. Full promotion of Hh signaling requires both the EGF-like domains of Shf and the WIF domains of either Wif1 or Shf. That the Wif1 WIF domain can increase the Hh promoting activity of Shf's EGF domains suggests it is capable of interacting with Hh. In fact, full-length Wif1 affected distribution and signaling of Hh in D. melanogaster, albeit weakly, suggesting a possible role for Wif1 as a modulator of vertebrate Hh signaling.